Pelaksanaan Pelatihan Bina Vokalia Di Purwa Caraka Music Studio Padang - Dina Yulia Pratiwi; Erfan Erfan (FBS Universitas Negeri Padang, 2021)
This research is motivated by the existence of a vocal instructor, who does not have a musical education background, at Purwa Caraka Music Studio Padang. However, he is able to bring his students to get achievement at national level. This study aims to determine and describe the implementation of vocal training at Purwa Caraka Music Studio Padang. The aspects explored in this study are: 1) The program of vocal training at Purwa Caraka Music Studio Padang, 2) The implementation of vocal training at Purwa Caraka Music Studio Padang, 3) Obstacles to the implementation of vocal training at Purwa Caraka Music Studio Padang.This research useda descriptive analytic method. The data were collected through observation, interviews, documentation, and literature study. The results show that the implementation of vocal training at Purwa Caraka Music Studio Padang is based on the curriculum and handbooks. The methods used in vocal training are lectures, individual approachesand exercises, as well as voice production exercises which include: posture and diaphragmatic breathing, articulation techniques, intonation techniques, resonance techniques, and phrasering techniques. The obstacles in the implementation of the vocal training at Purwa Caraka Music Studio Padang are: 1) Mood of the students; 2) tone and tempo blind of the students.